Educação Infantil e os desafios do trabalho docente durante a pandemia: relato de experiência - OLIVEIRA, Hellyna Viana (2023)
In this work, the purpose was to report the experiences of the students of the Degree Course in Pedagogy, year 2019 morning, in the Supervised Internship in Early Childhood Education during the Covid-19 pandemic in a public school in the municipality of Altamira – PA, Thus, our objective was to analyze the socialization process between the teacher, academics and the children of the Pré I class, problematizing the question:How did the socialization process occur during the internship and what are the difficulties experienced by the teacher, academics and students? The methodology used was the field research with the subsequence of the observation tool, participation and elaboration of a plan of activities that helped in the pedagogical preparation of attendance to the students of the classes of kindergarten I. Parallel to this, we made a literature review on the pedagogical practices in the time of pandemic in the area of early childhood education and also on the importance of the internship in the formation of the teacher. After data analysis, the results showed that despite the internship being remote, the pedagogy students were able to have this immersion in the reality of a classroom, because playful pedagogical materials, lesson plan and ornamentation of the classroom were produced to receive students in the return to classroom classes.